Knowledge, attitude and behaviour towards seasonal influenza: a community based study in rural Vadodara - Makwana, Bharati L.; Modi, Parth R.; Shringarpure, Kalpita S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Seasonal influenza, though contagious, is preventable, provided the community and its people are aware of its mode of transmission and basic steps of prevention. Methods: This was a cross-sectional descriptive study conducted in the rural field practice area of a Medical College Baroda in the month of February 2019, when the seasonal influenza cases were at its peak. A house to house survey was carried out to enquire about the knowledge, attitude, behavior related to seasonal influenza and its source of information. The structured questionnaire was based on the information, education and communication material displayed by the Health Department for the General Public. Respondents between the age of 15-60 years were interviewed after informed consent. Data-entry and analysis was done in Epi-Data software. Results: Out of 633 respondents, two-thirds of the respondents (427, 67.5%) were aware about seasonal influenza (swine flu). They were aware about common symptoms of flu such as cough, running nose and fever (43.8%, 43% and 41.4% respectively). Majority of those who knew about the flu were aware of it being preventable (59%); 37% knew it could be prevented by using a handkerchief, while 30% were aware about avoiding crowded places. Source of information was television (33%), followed by health care provider (14%) and newspaper (12%). Conclusions: Two-thirds of the respondents in the rural area were aware about seasonal influenza as a disease; majority of them knew that it could be prevented. The source of information was mainly media and health care providers. Attempts to improve the dissemination of information and behavior change communication is the way forward.